Mediterranean diet, sport and health - Laganà, Pasqualina; Coniglio, Maria Anna; Corso, Cesare; Lo Turco, Vincenzo; Dattilo, Giuseppe; Delia, Santi (Progress in Nutrition, 2020)
Among the environmental factors at the base of a good sporting performance there is a correct diet. It allows our body to develop harmoniously and to keep fit, in addiction it improves the sport performances. The Mediterranean Diet, with its nutritional characteristics, is a balanced diet, universally accepted and easily applicable. The nutrition of a sportsman is similar to that of other individuals with the exception of the total calories taken, which must adequately cover the plastic and energy needs of athletes. Even subjects with chronic diseases such as diabetes or tumors can achieve good performance and, with the necessary precautions, adhere to the food plan provided by the Mediterranean Diet. The aim of the work is to promote a correct lifestyle known for over half a century but still current.